Development of a Theoretical Model That Predicts Optothermal Energy Conversion of Gold Metallic Nanoparticles - Rafiei, Nahid; Alishah Aratboni, Hossein; Khosravi Khorashad, Larousse; Alemzadeh, Abbas; Shaji, Sadasivan; Morones Ramírez, José Rubén (American Chemical Society, 2020)
Gold nanoparticles (AuNPs) can be found in different shapes and sizes, which determine their chemical and physical characteristics. Physical and chemical properties of metallic NPs can be tuned by changing their shape, size, and surface chemistry; therefore, this has led to their use in a wide variety of applications in many industrial and academic sectors. One of the features of metallic NPs is their ability to act as optothermal energy converters, where they absorb light at a specific wavelength and heat up their local nanosurfaces. This feature has been used in many applications where metallic NPs get coupled with thermally responsive systems to trigger an optical response. In this study, we synthesized AuNPs that are spherical in shape with an average diameter of 20.07 nm. This work assessed simultaneously theoretical and experimental techniques to evaluate the different factors that affect heat generation at the surface of AuNPs when exposed to a specific light wavelength. The results indicated that laser power, concentration of AuNPs, time × laser power interaction, and time illumination, were the most important factors that contributed to the temperature change exhibited in the AuNPs solution. We report a regression model that allows predicting heat generation and temperature changes with residual standard errors of less than 4%. These results are highly relevant in the future design and development of applications where metallic NPs are incorporated into systems to induce a temperature change triggered by light exposure.